The correct answer is option C.
The solution is shown below:
(8 - 3i)(6 + 5i)
= 8(6 +5i) - 3i(6 + 5i)
= 48 + 40i - 18i - 15i²
= 22i + 48 - 15(-1)
= 22i + 48 + 15
= 22i + 63
= 63 + 22i
Answer:
1/2
Step-by-step explanation:
Answer:
n=0
Step-by-step explanation:
Clear parenthesis w/ distribution:
3(-7n+1)=-21n+3
Move everything over to one side:
6n+3=-21n+3
6n=21n Subtract the 3 on the right.
-15n=0 Subtract the 21.
n=0 Divide the -15.
I think is inside and then outside. Not sure
Hope this helps!
Divide the top number and the bottom number by a number they both have in common